A ring monopole quad band antenna loaded with metamaterial and slots for wireless applications - Basavalinga Swamy; C. M. Tavade; Kishan Singh (Bulletin of Electrical Engineering and Informatics, 2021)
The present wireless applications demand a compact, multi-operated, and stable radiation pattern antenna with good gain and impedance matching performance. To accomplish this requirement. In this paper, we propose a compact metamaterial structure loaded quad band antenna. The structural specifications/layout of the antenna consists of a circular ring monopole fed by a microstrip line. The ground part of the antenna is loaded with a metamaterial rectangular split-ring resonator (RSRR), an L-shaped slot, and two horizontally placed rectangular slots parallel to each other. No external matching circuit is utilized and impedance matching is solely controlled by the placement of slots. The antenna shows operation at 2.1 GHz (2.01-2.24 GHz, a bandwidth of 230 MHz (WLAN)), 4.5 GHz (4.35-4.66 GHz, a bandwidth of 310 MHz (C-band)), 5.5 GHz (5.37-5.77 GHz bandwidth of 400 MHz (WiMAX)), and 7.2 GHz (7.08-7.33 GHz, a bandwidth of 250 MHz (satellite band)). The antenna exhibits good gain and stable radiation pattern in both the plane and thus can be utilized for aforementioned applications.